Light revealing architecture form - the role of light in contemporary interpolation - Paunović Žarić, Sanja --; Radulović, Veljko --; Alihodžić Jašarović, Ema --; Murgul, Vera -- (Journal of Applied Engineering Science, 2016)
The paper provides an overview of the role of light (both daily and artificial) in façade treatment on the examples of contemporary interpolations. Design of façade with regard to the characteristics of light ranges from the response to natural elements of the context, via treatment of light as substance, the role of light in constructing and transforming architecture, the role of light in attracting attention, to the communicative and interactive role of light in media towns. Transposition of traditional language has been indicated, as universal response to the conditions of locality, by transforming their formal possibilities using new technological achievements.  Such architecture may be well interpolated and returned to the place and spirit of space. KEY WORDS: Light as a material, facade, Interpolation, media facades, daylight.
Keywords: Media facades; Daylight; Light as a material; interpolation; facades; Architecture; architectural form